(untitled) (Bangladesh Journal of Medical Science, 2022)
Objectives: Data regarding vitamin D level and status among categories of prediabetes are scarce in the literature. This study is aimed to determine the level and status of vitamin D among adults with prediabetes and its different categories. Materials and methods: This crosssectional study was carried out in 111 newly detected adults with prediabetes according to American Diabetes Association 2018 criteria and 74 matched healthy control (normal glucose tolerance). People with prediabetes were categorized into impaired glucose tolerance, impaired fasting glucose and their combination group. Participants were recruited consecutively from the Department of Endocrinology, BSMMU to measure serum 25 hydroxyvitamin D by high performance liquid chromatography and serum intact parathormone, calcium, albumin and phosphate by chemiluminescent enzyme-labeled immunometric assay. Results: Vitamin D level and status were not significantly different between people with prediabetes & control and also in different categories of prediabetes. Severe vitamin D deficiency was significantly higher in people with prediabetes (27.5% vs 10%, p= 0.05). There were no associations between different blood glucose levels with vitamin D among adults with prediabetes. Conclusions:Vitamin D was not associated with prediabetes or its categories. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 120-128